1992
DOI: 10.1523/jneurosci.12-07-02838.1992
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in calcium conductances contribute to the physiological maturation of cerebellar Purkinje neurons in culture

Abstract: The relationship between calcium conductances and developmental changes in the active and passive membrane properties of cerebellar Purkinje neurons from rats was studied in a culture model system by using current-clamp and voltage-clamp techniques. These cultures, at 6–21 d of age, represented the main period of morphological and physiological development of the Purkinje neuron. In the current-clamp studies, input resistance decreased and the current-voltage curve became more S-shaped as the neurons matured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
6
45
1
Order By: Relevance
“…Developmental changes in Ca 2ϩ current in neurons have been reported previously, but, in general, these reports have been limited either to changes in the magnitude of Ca 2ϩ current expression during development (Dourado and Dryer, 1992;Desarmenien et ., 1993) or to changes in the relative expression of low-voltage and high-voltage-activated current types (Yaari et al, 1987;Gottman et al, 1988;Kostyuk, 1989;McCobb et al, 1989;Thompson and Wong, 1991;Gruol et al, 1992;Mynlieff and Beam, 1992;Rothe and Grantyn, 1994;Lorenzon and Foehring, 1995). In contrast, we report the expression in embryonic neurons of a mixed pharmacologic type of high-voltage-activated current that is replaced by high-voltage-activated current types that are blocked selectively by -CgTX GVIA or dihydropyridine antagonists.…”
Section: Developmental Changes In Ca 2؉ Currentmentioning
confidence: 67%
“…Developmental changes in Ca 2ϩ current in neurons have been reported previously, but, in general, these reports have been limited either to changes in the magnitude of Ca 2ϩ current expression during development (Dourado and Dryer, 1992;Desarmenien et ., 1993) or to changes in the relative expression of low-voltage and high-voltage-activated current types (Yaari et al, 1987;Gottman et al, 1988;Kostyuk, 1989;McCobb et al, 1989;Thompson and Wong, 1991;Gruol et al, 1992;Mynlieff and Beam, 1992;Rothe and Grantyn, 1994;Lorenzon and Foehring, 1995). In contrast, we report the expression in embryonic neurons of a mixed pharmacologic type of high-voltage-activated current that is replaced by high-voltage-activated current types that are blocked selectively by -CgTX GVIA or dihydropyridine antagonists.…”
Section: Developmental Changes In Ca 2؉ Currentmentioning
confidence: 67%
“…Previous electrophysiological studies of cultured hippocampal or cerebellar neurons have noted an increase in voltage-gated Ca 2ϩ current with age in culture (Meyers and Barker, 1989;Gruol et al, 1992;Basarsky et al, 1994;Randall and Tsien, 1995), but the time-dependent relationship of Ca 2ϩ current to cell death has not been studied directly or for the extended periods examined in the present study. The finding of a significant positive temporal correlation between Ca 2ϩ current density and neuronal death suggests that increased Ca 2ϩ current and cell death may be functionally related (Fig.…”
Section: Relationship To Neuronal Deathmentioning
confidence: 77%
“…Critical developmental processes such as the appearance of neurotransmitters and ion channels, neurite outgrowth, synaptogenesis, and intrinsic firing patterns all depend in part on developmental changes in voltage-dependent C a 2ϩ conductances (Mattson and Kater, 1987;Gruol et al, 1992;Basarsky et al, 1994;Spitzer, 1994;Rusanescu et al, 1995;T urrigiano et al, 1995).…”
Section: Abstract: Hippocampal Neurons; Calcium Currents; Cell Deathmentioning
confidence: 99%
“…The dramatic changes that occur in calcium conductances during neuronal maturation suggest an underlying and equally dramatic change in the density and subtype of VDCC. Indeed, in cultured cerebellar Purkinje cells, studies have demonstrated that changes in calcium conductances were critical for neuronal maturation (53). More recently, important changes were observed in the expression and differential contribution of N-type and P/Q-type VDCC during synapse formation in cultured neurons (30 -32).…”
Section: Discussionmentioning
confidence: 99%